Constructing Cultural Heritage: A Faircloughian Critical Discourse Analysis of Wonderful Indonesia’s YouTube Video on Mentawai Tattoos - Windy Harsiwi; Ajie Wicaksono (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines how Indonesia, particularly the Mentawai indigenous culture, is linguistically represented in the Wonderful Indonesia official YouTube promotional video entitled “Mentawai: The Ancient Art of Indonesia’s Tattoos Heritage” using Fairclough’s (1992) Critical Discourse Analysis (CDA) framework. Despite the growing body of research on Wonderful Indonesia promotional content, studies employing a linguistically focused CDA on videos representing Indonesian indigenous cultures remain scarce, particularly those analyzing a single video in systematic textual depth. This study addresses that gap. Employing a qualitative case study approach, this study analyzes the textual dimension of the video, focusing on evaluative vocabulary (e.g., “imbued,” “ancient”), metaphor (“a story written on the skin”), inclusive pronoun use (“our feet touch the land”), and sensory language, to examine how Indonesia is constructed as an attractive cultural tourist destination. The findings reveal that the video deploys a coherent set of linguistic strategies that portray Indonesia as exotic, diverse, and spiritually rich, reflecting underlying ideological values related to national branding and soft power. The study also demonstrates how the promotional framing of indigenous cultural heritage raises critical concerns regarding commodification and the absence of indigenous voices. This study contributes to tourism discourse research in the Indonesian context and demonstrates the continued relevance of Fairclough’s three-dimensional framework for analyzing digital promotional media.